Effectiveness of brief group intervention in the harmful alcohol use in primary health care - Janaina Soares; Divane de Vargas (Universidade de São Paulo, 2019)
ABSTRACT OBJECTIVE To verify the effectiveness of brief group intervention, performed by nurses, in reducing the hazardous or harmful alcohol use in users of a primary health care service. METHODS Clinical and randomized trial with follow-up of three months. The sample had 180 individuals with a pattern of hazardous or harmful alcohol use, recruited in a Basic Health Unit in the city of São Paulo. A sociodemographic questionnaire and the Alcohol Use Disorders Identification Test (Audit) were applied. The experimental group underwent the Brief Group Intervention, which had four group sessions, with weekly meetings. The control group received an information leaflet about issues related to alcohol consumption. Both groups participated in the follow-up of three months. The linear mixed model was used for data analysis, in which a 5% significance level was adopted. RESULTS Forty-four individuals under hazardous or harmful alcohol use completed all phases of the research. The experimental group had a statistically significant reduction (p < 0.01) of about 10 points in Audit score after the brief group intervention [before BGI = 15.89 (SD = 6.62) - hazardous use; after BGI = 6.40 (SD = 5.05) - low hazardous use] maintaining the low hazardous use in follow-up [6.69 (SD = 6.38) - low hazardous use]. The control group had a statistically significant reduction (p ≤ 0.01) of about three points in Audit score [before BGI = 13.11 (SD = 4.54) - hazardous use; after BGI = 9.83 (SD = 5.54) - hazardous use] and in follow-up presented the mean score of 13.00 (SD = 5.70), indicative of hazardous use. Differences between the two groups (experimental group versus control group) in reduction of consumption were statistically significant (p ≤ 0.01). CONCLUSIONS Our evidence showed that the brief group intervention performed by the nurse in the primary health care context was effective to reduce alcohol consumption in individuals with patterns of hazardous or harmful use.